The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3747/co.20.1375
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemic of Human Papillomavirus and Oropharyngeal Cancer in a Canadian Population

Abstract: InterpretationThe present study is the first to provide direct evidence that hpv-related oropharyngeal cancer is increasing in incidence in a Canadian population. Given the long lag time between hpv infection and clinically apparent malignancy, oropharyngeal cancer will be a significant clinical problem for the foreseeable future despite vaccination efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 16 publications
5
77
1
Order By: Relevance
“…5 However, a study in London, Ontario, was restricted to patients with tonsillar cancer for whom a pathology specimen was available; 17 one study in Toronto included only 22 patients with oropharyngeal cancer; 18 other Toronto-based studies either took place before routine HPV testing 12 or focused on recurrent or metastatic disease; 19 and one study in Montréal analyzed patients with locally advanced cancer who were treated with primary chemoradiation and had a minimum 3-year follow-up. 20 A previous study of 1374 Ontario-based patients with oropharyngeal cancer suggested that 66% of cases were HPV-positive by 2010.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, a study in London, Ontario, was restricted to patients with tonsillar cancer for whom a pathology specimen was available; 17 one study in Toronto included only 22 patients with oropharyngeal cancer; 18 other Toronto-based studies either took place before routine HPV testing 12 or focused on recurrent or metastatic disease; 19 and one study in Montréal analyzed patients with locally advanced cancer who were treated with primary chemoradiation and had a minimum 3-year follow-up. 20 A previous study of 1374 Ontario-based patients with oropharyngeal cancer suggested that 66% of cases were HPV-positive by 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HPV positive (HPV+) HNSCC is increasing at an epidemic pace. 6,7 Importantly, HPV negative (HPV-) and HPV+ HNSCC are molecularly distinct, with a different spectrum of mutations. 8 HPV+ HNSCC also constitutively express viral oncogenes that deregulate cell growth and gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of oral STI transmission are becoming more widely known. For example, HPV has been linked to a rise in throat cancer (Chaturvedi et al, 2011;Nichols et al, 2013).…”
mentioning
confidence: 98%